질소산화물의 선택적 환원을 위한 안티모니 산화물 조촉매들의 표면특성 탐구 - 이석현; 김종식 (The Korean Ceramic Society, 2022)
It is widely accepted that Sb oxide promotes redox cycling feature and SO2 resistance of a catalyst utilized for selective catalytic NOX reduction (SCR) at low temperatures (≤300 ℃). However, promotive roles of Sb oxide have never been explored with the alteration of its crystal phases, which can be crucial to direct the overall acidic/redox characteristics and SCR performance of a catalyst along with its SO2 tolerance. In this regard, while implementing TiO2-supported Mn oxide (Mn) as a model catalyst, we successfully isolated Sb2O3 and Sb2O5 on Mn using wet impregnation and precipitation protocols, leading to produce Mn-Sb-I and Mn- Sb-P, respectively. The resulting catalysts were verified to have comparable acidic properties, yet, exhibit distinct redox traits, as evidenced by the greatest quantity of labile oxygens for Mn-Sb-I (Sb2O3) compared to Mn and Mn-Sb-P (Sb2O5). This leads to significant enhancement of SCR performance and SO2 resistance for Mn-Sb-I over the others.